The V2 receptor antagonist tolvaptan raises cytosolic calcium and prevents AQP2 trafficking and function: an in vitro and in vivo assessment. Issue 9 (21st March 2017) - Tamma, Grazia; Di Mise, Annarita; Ranieri, Marianna; Geller, Ari; Tamma, Roberto; Zallone, Alberta; Valenti, Giovanna
Abstract: Tolvaptan, a selective vasopressin V2 receptor antagonist, is a new generation diuretic. Its clinical efficacy is in principle due to impaired vasopressin‐regulated water reabsorption via aquaporin‐2 (AQP2). Nevertheless, no direct in vitro evidence that tolvaptan prevents AQP2‐mediated water transport, nor that this pathway is targeted in vivo in patients with syndrome of inappropriate antidiuresis (SIAD) has been provided. The effects of tolvaptan on the vasopressin–cAMP/PKA signalling cascade were investigated in MDCK cells expressing endogenous V2R and in mouse kidney. In MDCK, tolvaptan prevented dDAVP‐induced increase in ser256‐AQP2 and osmotic water permeability. A similar effect on ser256‐AQP2 was found in V1aR −/− mice, thus confirming the V2R selectively. Of note, calcium calibration in MDCK showed that tolvaptan per se caused calcium mobilization from the endoplasmic reticulum resulting in a significant increase in basal intracellular calcium. This effect was only observed in cells expressing the V2R, indicating that it requires the tolvaptan–V2R interaction. Consistent with this finding, tolvaptan partially reduced the increase in ser256‐AQP2 and the water permeability in response to forskolin, a direct activator of adenylyl cyclase (AC), suggesting that the increase in intracellular calcium is associated with an inhibition of the calcium‐inhibitable AC type VI. Furthermore, tolvaptan treatment reduced AQP2 excretion in two SIAD patients and normalized plasma sodium concentration. These data represent the first detailed demonstration of the central role of AQP2 blockade in the aquaretic effect of tolvaptan and underscore a novel effect in raising intracellular calcium that can be of significant clinical relevance.